A randomized trial of the efficacy and safety of quilizumab in adults with inadequately controlled allergic asthma. Issue 1 (December 2016) - Harris, Jeffrey; Maciuca, Romeo; Bradley, Mary; Cabanski, Christopher; Scheerens, Heleen; Lim, Jeremy; Cai, Fang; Kishnani, Mona; Liao, X.; Samineni, Divya; Zhu, Rui; Cochran, Colette; et al.
Abstract Background Quilizumab, a humanized IgG1 monoclonal antibody, targets the M1-prime segment of membrane-expressed IgE, leading to depletion of IgE-switched and memory B cells. In patients with mild asthma, quilizumab reduced serum IgE and attenuated the early and late asthmatic reaction following whole lung allergen challenge. This study evaluated the efficacy and safety of quilizumab in adults with allergic asthma, inadequately controlled despite high-dose inhaled corticosteroids (ICS) and a second controller. Methods Five hundred seventy-eight patients were randomized to monthly or quarterly dosing regimens of subcutaneous quilizumab or placebo for 36 weeks, with a 48-week safety follow-up. Quilizumab was evaluated for effects on the rate of asthma exacerbations, lung function, patient symptoms, serum IgE, and pharmacokinetics. Exploratory analyses were conducted on biomarker subgroups (periostin, blood eosinophils, serum IgE, and exhaled nitric oxide). Results Quilizumab was well tolerated and reduced serum total and allergen-specific IgE by 30–40 %, but had no impact on asthma exacerbations, lung function, or patient-reported symptom measures. At Week 36, the 300 mg monthly quilizumab group showed a 19.6 % reduction (p =  0.38) in the asthma exacerbation rate relative to placebo, but this was neither statistically nor clinically significant. Biomarker subgroups did not reveal meaningful efficacy benefits following quilizumab treatment. Conclusions Quilizumab had an acceptable safety profile and reduced serum IgE. However, targeting the IgE pathway via depletion of IgE-switched and memory B cells was not sufficient for a clinically meaningful benefit for adults with allergic asthma uncontrolled by standard therapy. Trial registration ClinicalTrials.gov NCT01582503